SPATIO-TEMPORAL EVOLUTION OF RICE PRODUCTION IN CHINA IN THE REFORM AND OPENING-UP PERIOD (POST-1978) AND INFLUENCING FACTORS - Zhiguang LIU; xinliang WANG (Journal of Animal and Plant Sciences, 2026)
This study is based on panel data from 31 provincial-level administrative regions in China, analyzing the Spatio-temporal evolution and driving factors of rice production in China from the beginning of China's Reform and Opening-up in 1978 to 2022. The methods employed include the spatial Gini coefficient, industrial concentration index, center of gravity migration, and global Moran's index. The results show that China's rice yield has experienced fluctuating growth, with industrial concentration and the spatial Gini coefficient first decreasing and then increasing, reflecting enhanced regional concentration. Meanwhile, the primary concentration of rice production has moved to the northeastern area. indicating significant changes in spatial distribution. Additionally, rice production exhibits strong spatial dependence, with high-yield areas tending to cluster. Factors such as non-agricultural employment opportunities, comparative benefits, mechanization levels, and yield per unit area significantly impact the scale of rice production. Based on these findings, this study proposes policy recommendations, including adjusting the planting structure, improving mechanization, enhancing market competitiveness, paying attention to the impact of non-agricultural employment, strengthening regional planning coordination, and formulating strategies to cope with climate change. These suggestions offer a scientific foundation and actionable insights for optimizing rice production regions, shaping relevant policies, and ensuring sustainable rice cultivation in China. They boost the sustainable progress of the rice sector and provide a fresh viewpoint on regional shifts in rice production.
Keywords: Rice production; Spatio-temporal evolution; Influencing factors; Spatial Durbin model